(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
The digital image, finally, inhabits the physical space of matter in what we call the record of the event, through the processual and conceptual development of a proven and unprecedented methodology of transfer on wax. After this practice, where the matrix is intangible, we reflect on the condition of the contemporary image, through the very creation in which an infinity of data, based on digitized images of photographs, are reconstructed and reinterpreted in a analog/digital transformation process. The transfer links the digitized image to a medium, in this case wax, giving a new meaning to the work.